1983
DOI: 10.1017/s0033291700047930
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the effects of intracerebral injection in the marmoset of cytopathic cerebrospinal fluid from patients with schizophrenia or neurological disease

Abstract: SynopsisIn experiments designed to investigate transmission, cerebrospinal fluid (CSF) from patients with schizophrenia and neurological disease (Huntington's chorea and multiple sclerosis) which had been found to induce cytopathic effects in human embryonic fibroblast cell culture was injected intracerebrally into mice, hamsters and marmosets (small New World primates). No evidence was obtained of transmission to mice or hamsters. A total of 15 marmosets (Callithrix jacchus) was injected intracerebrally with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1987
1987
1992
1992

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Behavioural observations were made on the animals during a period of 2\ years prior to injection and for 2 | years after injection. In an earlier study (Baker et al 1983/)) we found that animals injected with CPE + ve CSF became progressively more inactive when compared with those injected with non-cytopathic (CPE -ve) CSF from control patients. In the present study we were unable to replicate this finding.…”
Section: H F Baker 1 R M Ridley T J Crow and D A J Tyrrellmentioning
confidence: 79%
See 2 more Smart Citations
“…Behavioural observations were made on the animals during a period of 2\ years prior to injection and for 2 | years after injection. In an earlier study (Baker et al 1983/)) we found that animals injected with CPE + ve CSF became progressively more inactive when compared with those injected with non-cytopathic (CPE -ve) CSF from control patients. In the present study we were unable to replicate this finding.…”
Section: H F Baker 1 R M Ridley T J Crow and D A J Tyrrellmentioning
confidence: 79%
“…It should be noted, however, that two studies conducted independently using coded CSF samples have shown that the CPE is a reproducible phenomenon even after the samples have been stored for several years over liquid nitrogen (Tyrrell et al 1983;Taylor et al 1985 c). Also, cell death has been implicated in all the neuropsychiatric diseases which have provided cytopathic CSF and is particularly marked in Huntington's disease where 50 % of CSF samples were found to be cytopathic in tissue culture (Crow et al 1979;Baker et al 1983 a). The nature of the agent in CSF from patients with Huntington's disease and schizophrenia responsible for the cytopathic effect in cell culture remains obscure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tyrrell et al (1979) described a cytopathic effect on human embryonic fibroblasts of CSF from schizophrenic patients and from individuals with a number of neurodegenerative disorders, but were unable to passage the agent or inhibit its effect with metabolic or DNA and RNA antagonists. Intracerebral inoculation of marmosets with the cytotoxic CSF reportedly caused behavioral changes (Baker et al 1983). Cytopathic effects of schizophrenic CSF were also reported by Libikova (1983).…”
Section: Search For Virusmentioning
confidence: 99%
“…Baker et al (1983) in England reported that CSF from schizophrenic patients which caused CPE in cell cultures produced behavioral alterations when injected intracerebrally into marmosets. In collaboration with the Laboratory of Central Nervous System Studies, National Institute of Neurological and Communicative Disorders and Stroke (NINCDS), attempts were undertaken by Kaufmann et al (in press) to study laboratory animals into which post-mortem schizophrenic brain tissue had been intracerebrally injected.…”
Section: Direct Approachesmentioning
confidence: 99%